2018
DOI: 10.3389/fmicb.2018.02331
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Proton Motive Force Under Low-Aeration Alkaline Conditions in Alkaliphilic Bacteria

Abstract: In Mitchell’s chemiosmotic theory, a proton (H+) motive force across the membrane (Δp), generated by the respiratory chain, drives F1Fo-ATPase for ATP production in various organisms. The bulk-base chemiosmotic theory cannot account for ATP production in alkaliphilic bacteria. However, alkaliphiles thrive in environments with a H+ concentrations that are one-thousandth (ca. pH 10) the concentration required by neutralophiles. This situation is similar to the production of electricity by hydroelectric turbines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…M. alcaliphilum grows optimally at pH 9. Alkaliphilic organisms are typically characterized by highly negative membrane potentials (Matsuno et al, 2018; Ventosa, Nieto, & Oren, 1998), which allows them to drive ATP synthase against the proton concentration gradient (consistent with an intracellular pH lower than that of their environment, 7.5 in the case of Salinivibrio costicola (Ventosa et al, 1998). In this section we aim to elucidate the effects that an increased Na + gradient across the membrane can have on other key parameters governing the functioning of the respiratory chain (internal pH and membrane potential).…”
Section: Resultsmentioning
confidence: 99%
“…M. alcaliphilum grows optimally at pH 9. Alkaliphilic organisms are typically characterized by highly negative membrane potentials (Matsuno et al, 2018; Ventosa, Nieto, & Oren, 1998), which allows them to drive ATP synthase against the proton concentration gradient (consistent with an intracellular pH lower than that of their environment, 7.5 in the case of Salinivibrio costicola (Ventosa et al, 1998). In this section we aim to elucidate the effects that an increased Na + gradient across the membrane can have on other key parameters governing the functioning of the respiratory chain (internal pH and membrane potential).…”
Section: Resultsmentioning
confidence: 99%
“…As the disruption of ΔΨ, the probe would be released into the extracellular milieu and result in increased fluorescence. Conversely, the disruption of ΔpH would be compensated by increasing ΔΨ, resulting in enhanced DiSC 3 (5) uptake into the cytoplasmic membrane and therefore decreased fluorescence [ 48 ]. Our results showed that exposure of cells into varying concentrations of WW307 resulted in an immediate increase in DiSC 3 (5) fluorescence in a dose-dependent manner ( Figure 8 A,B), suggesting that WW307 selectively dissipated the ΔΨ component of the PMF.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the attraction of proton by the production of polyglutamic acid on the cell surface has been reported in Bacillus pseudofirmus OF4 cells [35,36]. It was suggested that such attraction of protons to the cell surface was associated with the formation of proton motive force across the membrane [36]. It is possible that the polyglutamate motif of GmMATE4 plays a similar role in attracting protons to the vacuolar membrane surface.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, based on the above examples, it could be deduced that glutamate residues play an important role in promoting proton affinity. In addition, the attraction of proton by the production of polyglutamic acid on the cell surface has been reported in Bacillus pseudofirmus OF4 cells [35,36]. It was suggested that such attraction of protons to the cell surface was associated with the formation of proton motive force across the membrane [36].…”
Section: Discussionmentioning
confidence: 97%